2023
DOI: 10.29219/fnr.v67.9256
|View full text |Cite
|
Sign up to set email alerts
|

Allium macrostemon whole extract ameliorates obesity-induced inflammation and endoplasmic reticulum stress in adipose tissue of high-fat diet-fed C57BL/6N mice

Abstract: Background: Obesity is a major risk factor for metabolic syndrome and a serious health concern worldwide. Various strategies exist to treat and prevent obesity, including dietary approaches using bioactive ingredients from natural sources. Objective: This study aimed to investigate the anti-obesity effect of whole-plant Allium macrostemon (also called as long-stamen chive) extract (AME) as a potential new functional food. Design: C57BL/6N mice were divided into three groups and fed either a control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…It is believed that polyphenols in AM extract are responsible for its biological function. We previously reported the results of HPLC analysis showing that the AM contained several phenolic compounds including ellagic acid, protocatechuic acid, catechin, ferulic acid, chlorogenic, p-coumaric acid, and caffeic acid which had anti-obesity, antioxidant and anti-in ammatory activities (Kim et al 2023). Herein, we further analyzed AM by UHPLC-mass spectrometry and molecular networking analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that polyphenols in AM extract are responsible for its biological function. We previously reported the results of HPLC analysis showing that the AM contained several phenolic compounds including ellagic acid, protocatechuic acid, catechin, ferulic acid, chlorogenic, p-coumaric acid, and caffeic acid which had anti-obesity, antioxidant and anti-in ammatory activities (Kim et al 2023). Herein, we further analyzed AM by UHPLC-mass spectrometry and molecular networking analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The yield was 8.53% of the initial dry weight of the Cibotium Rhizome. The final extract was stored at −20 • C until use [22].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Absorbance was monitored at 280 nm for protocatechuic acid, (+)-catechin hydrate, p-coumaric acid, and ellagic acid, and at 320 nm for chlorogenic acid, caffeic acid, and ferulic acid. The results were quantified using a curve corresponding to standard materials and are presented in micrograms per gram [22]. The quantitative curve equation for each standard is shown in Supplementary Table S1.…”
Section: Compound Analysis Of Ecr By Hplcmentioning
confidence: 99%
See 1 more Smart Citation
“…Allium macrostemon Bunge (AM), one of the plant species included in the Chinese Pharmacopoeia [23], is commonly grown in East Asia [24] and has shown a variety of beneficial effects, including lipid-lowering, antioxidant, and anti-obesity activities, in various study models, including in vitro, in vivo, and clinical systems [25][26][27][28][29]. Previously, we reported that AM whole extract (200 mg/kg BW daily) treatment ameliorates inflammation and endoplasmic reticulum stress in adipose tissue of HF diet-induced C57BL/6N mice [29]. Here, we hypothesized that the simultaneous exposure to HF and BPA from delivery containers and delivery foods in humans would be higher than before, as the delivery food culture increased rapidly as a result of COVID-19.…”
Section: Introductionmentioning
confidence: 99%